'Diplomacy is a feminine art': Feminised figurations of the diplomat. Issue 5 (6th December 2020) - Towns, Ann E.
Abstract: The aim of this article is to examine whether and how diplomacy may be gendered, symbolically and rhetorically, using US representations of diplomacy as a case. Prior scholarship on gender and contemporary diplomacy is sparse but has shown that the symbolic figure of 'the diplomat' has come to overlap tightly with 'man' and be associated with traits often attributed to masculinity. Inspired by queer international relations methods, relying on the concept of 'figuration' and focused on US news media and biographies of diplomats from the past decade, this article uncovers and examines a palette of feminised figurations also at play in US representations of diplomacy, including the diplomat as 'the "soft" non-fighter', 'the relationship builder', 'the gossip', 'the cookie-pusher', and 'the fancy Frenchman'. These feminised figurations alternate between configuring the diplomat as a woman and – more commonly – a (feminised) man. The analysis complicates rather than displaces existing claims, highlighting the importance of attention to slippages and challenges to dominant masculinised subject positions.